PARTICIPATION OF WOMEN IN DAIRY FARM PRACTICES UNDER SMALLHOLDER PRODUCTION SYSTEM IN PUNJAB, PAKISTAN - Z. Batool; H. M. Warriach; M. Ishaq; S. Latif; M. A. Rashid; A. Bhatti; N. Murtaza; S. Arif; P.C.Wynn (Journal of Animal and Plant Sciences, 2014)
Women play a significant role in smallholder production system in Pakistan. They actively participate in various activities relating to crop and livestock production in addition to conducting their routine domestic duties often working non-stop from dawn to dusk. But the extent of their participation varies from region to region. The aim of this field survey was to investigate the involvement of women in dairy farm practices under small holder production system and possible factors affecting their participation in two districts of Punjab. A questionnaire was designed to collect the data from female farmers (n=194) from the districts of Bhakkar and Jhelum. Results indicate that the participation of women in dairy farm practices was significantly higher (P< 0.05) in Bhakkar than in district Jhelum. The present study suggests that, in order to maximize the smallholder dairy farm productivity, a strong extension program needs to be implemented to enhance the skills and knowledge of women.
Keywords: Women; dairy farm practices; smallholder